Comprehensive system of risk management of investment projects (Journal of Economic Research & Business Administration, 2016)
The practice of investment projects shows that most of the projects are usually completed in violation of the terms, cost overruns, which in turn leads to a weakening of the market position of enterprises. Special conditions of uncertainty are observed in the field of building production, where the complex and at the same time unique designs influenced by a variety of risk factors.For such projects in order to make the best decisions requires a systematic monitoring of risks which arise and which are beyond the control of the project participants. An effective сomprehensive system of risk management which includes risk analysis, planning, and risk management will help to improve the system of management of investment projects in conditions of risk. The article discusses the risks, systematized in the context of business processes in integrated risk management of investment projects.
Keywords: enterprise market strategy; fiscal and monetary risks; social andpolitical risks; business processes; macroeconomic risks